Medieval Monuments of Central Asia - Kelly, Gavin.
1 online resource (341 pages)
Keywords: This is a comprehensive study of the surviving monuments of the Qarakhanids - an important yet little-known medieval dynasty that ruled much of Central Asia between the late 10th and early 13th centuries.